Christian family as basis for civil society - Katarzyna Wrońska (Nicolaus Copernicus University in Toruń, 2014)
This text is an attempt to describe mutual relations between family and civil society in Polish reality. It does research work on historical and cultural conditions for faint rootedness of civic attitudes and commitment in our society. It poses a question on causes of low level of social trust and describes Polish familism in their mutual relation. It takes into consideration the role of Catholic Church as the institution which is constantly and deeply present in the life of most polish families and has much influence. This context indicates that there are both a possibility and need to build a Christian civil society in Poland. A new formula of parish as a community of communities is its exemplification. Activity of Church and other agents of public life (mainly: local authorities, media, educational institutions, NGO's, government, works and employers) in support of civil society in our country is an attempt to strengthen, beside the bonding capital necessary in the family and national life, the bridging capital which enables to build the new social ties and commitments basing on mutual trust, benevolence and cooperation with others.